Measuring the growth rate of UK dairy heifers to improve future productivity. (June 2016) - Bazeley, Katrine J.; Barrett, David C.; Williams, Paul D.; Reyher, Kristen K.
Highlights: This study monitored heifer growth on 20 farms in SW England under a variety of husbandry and feeding systems. Heifer growth was poor in the first month of life. Overall, heifer growth was very variable, especially in some of the herds studied. Poor growth rates in heifers on some units mean that many heifers never achieve their potential. Abstract: Sub-optimal heifer growth is associated with higher disease rates and reduced future performance and longevity in the dairy herd. This report describes a system for measuring heifer growth from birth to first calving that was used on commercial dairy farms in South West England, in order to gather benchmarking data to feed back to farmers. Weights ( n = 8443) were collected from 20 farms. There was a marked variation in individual and herd mean growth rates. Overall, calves gained no weight in the first 8 days after birth and had a very low growth rate (median 0.12 kg/day) up to 30 days, a period when feed conversion efficiency is high and calves are vulnerable to disease. Heifers whose growth rate up to 180 days was low were significantly less likely to achieve target service weight (374 kg) by 420 days. Monitoring heifer growth during the rearing period enables farmers to improve heifer growth rates and so impact both the efficiency of heifer rearing and, potentially, the productivity and performance of the adult herd.